2020
DOI: 10.1007/s13202-020-01003-2
|View full text |Cite
|
Sign up to set email alerts
|

A review of molecular dynamics simulations in the designing of effective shale inhibitors: application for drilling with water-based drilling fluids

Abstract: When drilling for oil and gas, maintaining wellbore stability is of primary importance to reduce non-productive time and trouble cost. Shale swelling causes many problems related to stability when drilling with water-based drilling fluids (WBDF). For many years, it remains the number one cause of time wastage and well abandonment. Different shale samples have different chemical compositions that affect their behavior when in contact with water. This factor makes laboratory-based analysis and characterization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 89 publications
(135 reference statements)
0
7
0
Order By: Relevance
“…Osmotic swelling results in more massive overall volume increases than crystalline swelling (Swai et al, 2020). Molecular simulation is a numerical simulation technique based on the molecular (atomic) scale, which can be well applied to study the microscopic properties of matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osmotic swelling results in more massive overall volume increases than crystalline swelling (Swai et al, 2020). Molecular simulation is a numerical simulation technique based on the molecular (atomic) scale, which can be well applied to study the microscopic properties of matter.…”
Section: Introductionmentioning
confidence: 99%
“…Crystalline swelling increases the volume of the mineral , whilst osmotic swelling can increase the interlayer spacing from 20 to 130 Å and can cause macroscopic expansion of the soil (Schmidt et al, 2005;Nehdi, 2014). Osmotic swelling results in more massive overall volume increases than crystalline swelling (Swai, 2020). Molecular simulation is a numerical simulation technique focused on the molecular (atomic) scale that can be applied to the study of the microscopic properties of matter.…”
mentioning
confidence: 99%
“…Drilling fluid is circulated from the surface, through the drill pipe to the bit face; it lifts the generated cuttings and brings them to the surface, where separation equipment removes the cuttings from the drilling fluid, which is circulated, with the help of powerful pumps, back to the wellbore [11,13]. Drilling fluids perform additional functions [11,[13][14][15]; mainly, they control subsurface pressures, stabilize the exposed rock, prevent contamination of subsurface formation hydrocarbon fluids, provide buoyancy, and cool and lubricate the bit. Such fluids must be engineered so that they can perform efficiently in harsh environments, and it must be ensured that they do not damage the formations which are being drilled.…”
Section: Introductionmentioning
confidence: 99%
“…Shales in some offshore formations, especially in deep-sea formations, have strong water sensitivity. Since it is prone to hydration expansion and dispersion on exposure to free water in drilling fluids, it can cause wellbore instability (Liu et al 2020;Swai 2020;Van Oort 2003). In addition, the temperature around the mudline in deep-sea regions is as low as 2-4 °C, or even below 0 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Years of research and field practices have indicated that the research and development of highly efficient hydration inhibitor along with the use of polymeric coating agent could achieve an effective inhibition of shale hydration (Marin et al 2009;Swai 2020). The coating agent is usually the high-molecular-weight amide polymer, such as partially hydrolyzed polyacrylamide (HPAM) and polyacrylamide (PAM) (Jain and Mahto 2015;Kadaster et al 1992;Mehtar et al 2010;Van Oort 2003).…”
Section: Introductionmentioning
confidence: 99%